Promoting Religious Moderation in New Media: Between Contestation and Claiming Religious Authority - Mahmud Yunus; Firmanda Taufiq; Ahalla Tsauro (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
Mainstreaming religious moderation has become crucial for Indonesian Muslims, particularly in the digital era. Experts agree that digital media is the most efficient and effective way of achieving this issue. To better understand the representation of Islam in Indonesia's digital sphere, this article aims to analyze content production by NU and Muhammadiyah, two of Indonesia's most prominent Islamic organizations. Using a Netnography approach and website analysis by Similarweb.com, this article analyzed the website's traffic, audience demographics (covering age and gender), and global standing. This information is used to investigate which social media network is most suited to disseminate ideas for religious moderation. According to the up-to-date statistics, nu.or.id is currently globally ranked 18,914, which places it well above muhammadiyah.or.id, which is positioned at the far more distant position of 140,435. Comparing December 2022 traffic and engagement statistics, nu.or.id had 4.169 million more visitors than muhammadiyah.or.id with 503,163 thousand visitors. The top country such as Indonesia, Malaysia, the United States, Singapore, and Germany perform admirably. The two sides are statistically about even when looking at viewer demographics. Based on these metrics, content created by nu.or.id that promotes religious moderation has a more powerful of being shared extensively. We believe there is potential for a stronger impact on mainstreaming religious moderation in Indonesia and globally if these two organizational platforms are integrated.